Le Romantisme français au 19ème siècle : Un mouvement littéraire et culturel majeur (Sirte University Journal of Humanities, 2024)
Romanticism, a literary, artistic, and cultural movement that emerged in France at the beginning of the 19th century, was a reaction against the rigid rules of classicism and the cold rationality of the Enlightenment. It emphasizes emotion, individualism, nature, and subjectivity, and explores various themes such as the exaltation of love, nostalgia for the past, political and social revolt, as well as the contemplation of nature. Romanticism marked a decisive turning point in the evolution of literature and art in France, profoundly influencing not only writers, but also painters, musicians, and playwrights.
Keywords: Romantisme; 19ème; Culturel; alcherif; 2024